Sucralose enhances GLP-1 release and lowers blood glucose in the presence of carbohydrate in healthy subjects but not in patients with type 2 diabetes - YAVUZ, DİLEK; HAKLAR, GONCAGÜL; ŞİRİKÇİ, ÖNDER (NATURE PUBLISHING GROUP, 2015)
BACKGROUND/OBJECTIVE: Artificial sweeteners were thought to be metabolically inactive, but after demonstrating that the gustatory mechanism was also localized in the small intestine, suspicions about the metabolic effects of artificial sweeteners have emerged. The objective of this study was to determine the effect of artificial sweeteners (aspartame and sucralose) on blood glucose, insulin, c-peptide and glucagon-like peptide-1 (GLP-1) levels. SUBJECTS/METHODS: Eight newly diagnosed drug-naive type 2 diabetic patients (mean age 51.5 +/- 9.2 years; F/M: 4/4) and eight healthy subjects (mean age 45.0 +/- 4.1 years; F/M: 4/4) underwent 75 g oral glucose tolerance test (OGTT). During OGTT, glucose, insulin, c-peptide and GLP-1 were measured at 15-min intervals for 120 min. The OGTTs were performed at three settings on different days, where subjects were given 72 mg of aspartame and 24 mg of sucralose in 200 ml of water or 200 ml of water alone 15 min before OGTT in a single-blinded randomized order. RESULTS: In healthy subjects, the total area under the curve (AUC) of glucose was statistically significantly lower in the sucralose setting than in the water setting (P = 0.002). There was no difference between the aspartame setting and the water setting (P = 0.53). Total AUC of insulin and c-peptide was similar in aspartame, sucralose and water settings. Total AUC of GLP-1 was significantly higher in the sucralose setting than in the water setting (P = 0.04). Total AUC values of glucose, insulin, c-peptide and GLP-1 were not statistically different in three settings in type 2 diabetic patients. CONCLUSIONS: Sucralose enhances GLP-1 release and lowers blood glucose in the presence of carbohydrate in healthy subjects but not in newly diagnosed type 2 diabetic patients.
Keywords: ARTIFICIAL SWEETENER; TASTE RECEPTORS; ORAL GLUCOSE; ABSORPTION; EXPRESSION; GUSTDUCIN; HORMONES; HUMANS; CELLS